Mucinous breast carcinoma metastatic to thyroid gland: Report of a case diagnosed by fine‐needle aspiration cytology. Issue 5 (17th February 2020) - Wang, Meixian; Liu, Xiulan; Wei, Bing; Liu, Nian; Li, Qiyuan; Su, Xueying
Abstract: Mucinous breast cancer is a slow‐growing neoplasm, which has fewer lymph node metastases and favorable prognosis compared with invasive breast cancer no special type. The hematogenous spread of breast mucinous carcinoma is very rare. Though breast cancer involving thyroid has been reported before, there is still no report about thyroid metastatic breast mucinous carcinoma in the literature. Recently by performing thyroid fine‐needle aspiration, a 58‐year‐old woman who had breast cancer 13 years ago was diagnosed as thyroid metastatic mucinous breast carcinoma, cellular variant with neuroendocrine differentiation. For this patient, the thyroid was the only involved site without widespread metastatic diseases, so thyroidectomy and the right cervical lymph nodes dissection were performed to make better survival. As a result, the patient had not shown any signs of recurrence 9 months after the thyroid surgery.